EPILEPSY AT ADULTS: GENDER COMORBIDE DISORDERS, APPLICATION OF VALPROATES - P. N. Vlasov (Эпилепсия и пароксизмальные состояния, 2016)
Was carried out the analysis of basic somatic and reproductive disorders at adults’ epilepsy, as well as the role of valproates in the epilepsy therapy at the modern stage. The individual therapy of adults’ epilepsy along with forms of epilepsy/types of epileptic attacks, should mandatory take into account such things as somatic pathology, sexual function and the condition of the emotional-volitional sphere. The valproic acis remains the substance, referred to the first choice group in the treatment of idiopathic (generalized/focal) cryptogenic/symptomatic focal and non-differentiated epilepsies at patients from different age groups with broad spectrum of the accompanying somatic pathology and at men. The valporate is the selection choice at renal failures, kidney transplantation, heart diseases, pulmonary pathologies, brain tumors, different psychic disorders. The substance is not recommended in case of liver diseases with its decompensation, of the bone marrow and liver transplantation, porphyria, adiposity and during pregnancy. For women the valproic acid is applied with reserve in case of the inefficiency of other AED with mandatory information of the patient on possible consequences of the substance application.